Impact of Geological Structures on Rock Slope Stability in The NW Nose (Plunge ) of Surdash Anticline, Sulaimaniya/ NE Iraq - Hussien, Summood A.; Al-Kubaisi, Manal Sh.; Hamasur, Ghafor A. (Iraqi Journal of Science, 2020)
The road network in Surdash anticline is considered as an important road network connecting lower Dukan town with the touristic upper Dukan town. Dukan lake plays an important role in the social and economic activities of Dukan town and the surrounding areas.For assessing the stability of the rock slopes in the area, 9 stations were selected along the upper Dukan road on both sides of Surdash anticline, and their stability was evaluated by the kinematic analysis using DIPS V6.008 software. Kinematic analysis of the studied stations shows thatplanar sliding is possible in stations No. 1, 2, 3 and 8, while wedge sliding is possible in station No. 5, 6, 7 and 9b. The other stations (No. 4and 9a) are stable. Tectonic structures played an extra paradoxical role in the stability of the rock slopes and the type of failure. In most ofthe selected stations , the geological structure had a negative role, which supported or promoted the failure in the study area. However, in few stations , it had a positive role and converted the slope from unstable to stable conditions. In addition, the presence of incongruent minor syncline folds, especially in the SW-limb of themajor anticline, led to the occurring of wedge sliding instead of plane sliding.